Mathematical models for magnetic particle imaging. (12th June 2018) - Kluth, Tobias
Abstract: Magnetic particle imaging (MPI) is a relatively new imaging modality. The nonlinear magnetization behavior of nanoparticles in an applied magnetic field is exploited to reconstruct an image of the concentration of nanoparticles. Finding a sufficiently accurate model to reflect the behavior of large numbers of particles for MPI remains an open problem. As such, reconstruction is still computed using a measured forward operator obtained in a time-consuming calibration process. The model commonly used to illustrate the imaging methodology and obtain first model-based reconstructions relies on substantial model simplifications. By neglecting particle–particle interactions, the forward operator can be expressed by a Fredholm integral operator of the first kind when describing the inverse problem. Here, we review previously proposed models derived from single-particle behavior in the MPI context and consider future research on linear and nonlinear problems beyond concentration reconstruction applications. This survey complements a recent topical review on MPI (Knopp et al 2017 Phys. Med. Biol .62 R124).